Individual and organizational factors associated with disaster preparedness and resilience among Indonesian hospital nurses: a cross-sectional study - Winarti, Wiwin; Barbara, Laksita; Simatupang, Ronny Basirun; Hasena, Siti Luthfiana; Dielfanie, VK (Jurnal Ners, 2024)
Introduction: The significance of nurses' disaster preparedness and resilience in diverse settings has become increasingly apparent due to the rise in global crises. This study aimed to investigate nurses' perspectives on these two factors and to examine their intricate relationships and nuances. Methods: A cross-sectional framework was used to evaluate 390 nurses using the Disaster Preparedness Evaluation Tool (DPET) and the Connor-Davidson Resilience Scale (CD-RISC). Descriptive statistics, Mann-Whitney U-test, Kruskal-Wallis H test, Spearman's correlation analysis, and the generalized linear model were employed to determine the relationships between nurses' characteristics, self-regulation, work culture perception, and their DPET and CD-RISC scores. Results: The results revealed that 79.7% of the participants were female, but male nurses consistently scored higher on both the assessments. The average DPET score was 172.29, and the average CD-RISC score was 27.34. Self-regulation and work culture perception were the most influential factors in raising DPET and CD-RISC scores by 4.032 and 1.454 units (p=0.000), and 1.112 and 0.34 units (p=0.000). Conclusions: This study emphasizes the need for ongoing training of nurses in disaster preparedness and resilience to promote introspective learning and collaborative best practices. It also highlights the role of hospitals in optimizing resources and creating a supportive environment for enhanced disaster preparedness and resilience, given the impact of organizational work culture. The study findings suggest a nuanced understanding of gender dynamics in disaster preparedness and resilience, emphasizing the importance of further exploration of these disparities for effective nursing practices.